2013
DOI: 10.5301/hip.2013.10878
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Iliotibial Band Release in Snapping Hip

Abstract: Several open surgical techniques have been used to treat recalcitrant cases of snapping iliotibial band with varying results. Recently, endoscopic techniques have become available. The purpose of this study was to investigate the results of a modified endoscopic iliotibial band release using a longitudinal retrospective case series.
 Fifteen patients (three men and 12 women) with symptomatic external snapping hip were treated with an endoscopic release of the iliotibial band. The average age was 25 years (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 25 publications
(59 reference statements)
0
58
0
Order By: Relevance
“…A study by Strauss et al found that the repetitive snapping of the ITB in external coxa sultans and overuse of the ITB can result in a thickened ITB and trochanteric bursitis [ 2 ]. Trochanteric bursitis and thickened ITB are both associated with inflammation brought on by repetitive rubbing and friction to the anterior/lateral/or posterior facet by the ITB [ 12 ]. During the gait cycle snapping is exacerbated during flexion when the ITB is maximally stretched [ 13 ] and slides anteriorly over the greater trochanter, and repeats extension as the ITB moves posteriorly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Strauss et al found that the repetitive snapping of the ITB in external coxa sultans and overuse of the ITB can result in a thickened ITB and trochanteric bursitis [ 2 ]. Trochanteric bursitis and thickened ITB are both associated with inflammation brought on by repetitive rubbing and friction to the anterior/lateral/or posterior facet by the ITB [ 12 ]. During the gait cycle snapping is exacerbated during flexion when the ITB is maximally stretched [ 13 ] and slides anteriorly over the greater trochanter, and repeats extension as the ITB moves posteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…Weakness in the gluteal or tensor facia latae muscles precipitates hip internal rotation resulting in increased strain in the ITB and consequent friction with the greater trochanter during movement [ 22 ]. A study conducted on ITB releases for snapping hip patients reported favorable outcomes through gluteal and abductor muscle strengthening [ 12 ]. An additional study started patients on a 6-week abductor strengthening physical therapy regimen and reported no pain in 91% of subjects at 6-month follow up [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main indications are related to the presence of periprosthetic psoas tendonitis, instability, 36 or persistent pain without a clear cause. [37][38][39][40] Using arthroscopy for hip arthroplasty is considered a central compartment procedure, 4 but a primary approach to the . With the hip in traction, adequate joint distraction was observed, but the deformity hindered the approach to the central compartment (B).…”
Section: Painful Hip Arthroplastymentioning
confidence: 99%
“…In its initial conception, these 2 compartments were addressed differently, and, characteristically, the peripheral compartment was ac-cessible without the need to establish traction. 1,2 This division in central and peripheral compartments is artificial, and in most cases, both compartments need to be evaluated and accessed sequentially, 3,4 although the procedures are usually started through the central compartment. 5,6 Recently, a lateral compartment around the hip joint has also been used to assess peritrochanteric and sciatic pathology.…”
mentioning
confidence: 99%
“… 2 , 3 , 4 , 5 , 6 Friction of a tighten iliotibial band (ITB) over the greater trochanter (GT) seems to be a direct cause of the snapping phenomenon and becomes painful as the GT bursa becomes inflamed. 1 , 2 , 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 Several pathologies, including postural defects, the hip joint bony anatomy, and ITB structure are taken into consideration as a possible reason for tightening of the ITB. 2 , 9 , 10 These pathologies should be precisely diagnosed and addressed during physiotherapy treatment.…”
mentioning
confidence: 99%